2022
DOI: 10.1161/circep.121.010636
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Oligomers Cause Proarrhythmic Metabolic and Electrophysiological Effects in Atrial Myocytes

Abstract: Background: With aging, the human atrium invariably develops amyloid composed of ANP (atrial natriuretic peptide) and BNP (B-type natriuretic peptide). Preamyloid oligomers are the primary cytotoxic species in amyloidosis, and they accumulate in the atrium during human hypertension and a murine hypertensive model of atrial fibrillation susceptibility. We tested the hypothesis that preamyloid oligomers derived from natriuretic peptides cause cytotoxic and electrophysiological effects in atrial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Indeed, specific mutations in the ANP gene are known to be associated with increased susceptibility to AF and known forms [ 38 ]. Accordingly, Yang et al [ 39 ] showed that ANP oligomers exert detrimental effects on the electrical properties of atrial cells and that this phenomenon is enhanced in the presence of mutant ANP. These findings are corroborated by Hua and colleagues [ 40 ], who confirmed an increased susceptibility to the development of AF in an animal model with mutant ANP.…”
Section: The Role Of Anp In Atrial Fibrillationmentioning
confidence: 99%
“…Indeed, specific mutations in the ANP gene are known to be associated with increased susceptibility to AF and known forms [ 38 ]. Accordingly, Yang et al [ 39 ] showed that ANP oligomers exert detrimental effects on the electrical properties of atrial cells and that this phenomenon is enhanced in the presence of mutant ANP. These findings are corroborated by Hua and colleagues [ 40 ], who confirmed an increased susceptibility to the development of AF in an animal model with mutant ANP.…”
Section: The Role Of Anp In Atrial Fibrillationmentioning
confidence: 99%
“…Increased ANP production is meant to normalize haemodynamics through natriuresis and vasodilatation, 53 but ultimately becomes maladaptive as ANP tends to accumulate in the atria. It has recently been reported that pre‐fibrillary species cause cytotoxic and electrophysiological effects in atrial cells that promote arrhythmia susceptibility 54 . The role of atrial amyloidosis as an arrhythmogenic substrate for persistent or permanent AF is well established 4 .…”
Section: Isolated Atrial Amyloidosismentioning
confidence: 99%
“…The aging human atrium invariably develops amyloid composed of ANP and to a lower extent B-type natriuretic peptide, but this accumulation remains limited and non-clinically significant unless it is enhanced by atrial stretch due to ventricular diastolic dysfunction, mitral valve disease and/or AF. Increased 54 The role of atrial amyloidosis as an arrhythmogenic substrate for persistent or permanent AF is well established. 4 While the mechanisms relating atrial amyloidosis to AF (inhomogeneous impulse propagation and fragmentation of atrial activation into multiple wavelets) have not been specifically studied in relation to ANP accumulation, we may speculate that ANP atrial amyloidosis is a determinant of atrial remodelling due to AF, and a mechanism whereby AF begets AF 55 (Figure 6 and Graphical Abstract).…”
Section: Isolated Atrial Amyloidosismentioning
confidence: 99%
“…However, under disease conditions, the increased plasma level of ANP is often associated with heart failure and hypertension, thus ANP also serves as a biomarker for the diagnosis and treatment of heart failure. More importantly, ANP tends to accumulate on the surface of atrial myocytes to form β-structure-rich, amyloid-like aggregates, i.e., isolated atrial amyloid (IAA). , Apart from similar amyloid-like structures between ANP and Aβ, both ANP and Aβ are known to cause age-associated amyloidosis and found to co-exist in blood circulation, , which increases the possibilities for their cross-seeding or co-aggregation with other amyloid proteins …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, ANP tends to accumulate on the surface of atrial myocytes to form β-structure-rich, amyloid-like aggregates, i.e., isolated atrial amyloid (IAA). 29,30 Apart from similar amyloid-like structures between ANP and Aβ, 31 both ANP and Aβ are known to cause age-associated amyloidosis 32 and found to coexist in blood circulation, 33,34 which increases the possibilities for their cross-seeding or co-aggregation with other amyloid proteins. 35 To test the abovementioned hypothesis, we examined the potential cross-seeding between ANP and Aβ and the crossseeding impacts on Aβ aggregation and toxicity in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%